Magnitude of malnutrition among underfive children in urban slums of commercial capital of India and its multifactorial causation: A community-based study - Kiran S Akhade (Journal of Family Medicine and Primary Care, 2019)
Context: Malnutrition in children is common globally and may result in both short- and long-term irreversible negative health outcomes. It is not a simple disease with single causative factor but it is a disease with multifactorial causation. Aims: 1) To estimate prevalence of malnutrition in underfive children using “Z” score. 2) To evaluate the role of epidemiological and maternal factors on the nutritional status of children. Settings and Design: Community-based cross-sectional study. Methods and Materials: Randomly 10 slums were selected and under five-year-old children and their mothers from urban slums were examined and interviewed. Statistical Analysis: Data was analyzed with SPSS ver 20 and appropriate tests were applied. Results: Four-hundred children were examined. According to Z score classification, 39.8%, 36.5%, and 24.8% of children are underweight, stunted, and wasted, respectively. Family size (P = 0.02, χ2 = 7.7), initiation of breastfeeding (P = 0.009, χ2 = 6.8), maternal education (P = 0.001, χ2 = 13.9), underweight mothers (P = 0.05, χ2 = 4.8), and maternal dietary intake (P = 0.03, χ2 = 6.5) are significantly associated with underweight children. Similarly, stunted children show strong association with increasing age of child (P = 0.001, χ2 = 18.1), birth weight (P = 0.006, χ2 = 7.6), and not seeking medical opinion (P = 0.03, χ2 = 7.0). Primary immunization (P = 0.05, χ2 = 3.5), maternal education (P = 0.002, χ2 = 12.4), employed mothers (P = 0.02, χ2 = 4.9), and underweight mothers (P = 0.05, χ2 = 5.3) are associated with wasting in children. Conclusions: This study reveals very high prevalence of malnutrition status among underfive children of urban slums of commercial capital of India. Various maternal and epidemiological factors affect child nutritional status.